Spectral and energy efficiency with satisfaction constraints - Mauricio, Weskley Vinicius Fernandes (2014)
In this article we revisit the Radio Resource Allocation (RRA) problem of maximizing the total transmit data rate subject to satisfaction guarantees. It was previously studied on the perspective of Resource Block (RB) assignment (only) considering Equal Power Allocation (EPA) and, herein, we study this problem assuming adaptive power allocation. Two power allocation strategies are proposed and shown to be able to achieve energy and/or spectral efficiency gains compared to the original solution proposed in the literature. While the first power allocation strategy is capable of saving a considerable amount of transmit power maintaining the same transmit data rate of EPA, thus obtaining energy efficiency gains, the second strategy is able to convert this energy efficiency gain in spectral efficiency.